Observation of symptomatic thromboembolic events in endoscopic retrograde cholangiopancreatography patients with interruption of antithrombotic therapies - Wu, Jinqing; Hong, Jianglong; Ding, Hao; Mei, Qiao (Frontiers in Medicine, 2025)
Background and objectivesAn increasing number of patients with antithrombotic therapies are undergoing endoscopic retrograde cholangiopancreatography (ERCP). Interruption of antithrombotic therapies may be associated with a higher risk of symptomatic thromboembolic (TE) events. We aimed to investigate the risk of symptomatic TE events among patients undergoing ERCP.MethodsA retrospective cohort study on patients at risk for symptomatic TE events who had undergone ERCP from January 2016 to October 2023 was conducted. A total of 2,482 patients who had undergone ERCP were included in this study. We compared the risk of symptomatic TE events within 30 days after ERCP between the group treated with antithrombotic agent and the group not treated with antithrombotic agent using multivariate regression analysis adjusted for covariates.ResultsA total of 15 patients (0.60%, 15/2,482) developed symptomatic TE events within 30 days after ERCP. The symptomatic TE event rate in subjects on any antithrombotic drug was 1.46% with an odds ratio (OR) of 5.267 (n = 689, 95% CI 1.79–15.46, p = 0.002), compared with those not treated with antithrombotic drugs (n = 1,793). The symptomatic TE event rate in subjects on temporary interruption of antithrombotic drugs was 1.48% with an OR of 5.36 (n = 677, 95% CI 1.83–15.74, p = 0.002), compared with those not treated with antithrombotic drugs (n = 1,793). Multivariate regression analysis indicated that patients with high-risk conditions had a significantly higher risk of post-ERCP symptomatic TE events (adjusted OR 11.73, 95% CI 2.23–61.70).ConclusionInterruption of antithrombotic drugs is associated with higher post-ERCP symptomatic TE events, particularly in high-risk conditions.